Metallo-β Lactamase Producing Non-Fermentative Gram-Negative Bacilli from Various Clinical Isolates in a Tertiary Care Hospital: A Descriptive Cross-sectional Study - Mahendra Shrestha; Ratna Baral; Lok Bahadur Shrestha (Journal of Nepal Medical Association, 2021)
Introduction: Non-fermentative gram-negative bacilli are common causes of human infections especially nosocomial infections. These organisms are usually resistant to multiple antimicrobial agents including carbapenems. The study aimed to find out the prevalence of metallo-β-lactamase producing non-fermentative gram-negative bacilli among the samples which yielded growth of bacteria in a tertiary care hospital.